ACCESSORY AURICLE AND HEMIFACIAL MICROSOMIA IN A ONE-YEAR-OLD PATIENT: A CASE REPORT WITH SCOPING REVIEW - Ulfa Elfiah; Gita Anggraini Nur Rohmah; Galang Cahyo Pamungkas (Universitas Airlangga, 2026)
Highlights: Infants with accessory auricles should undergo careful clinical evaluation to determine whether the condition is part of a syndrome or an isolated congenital anomaly. In hemifacial microsomia without functional impairment, observation is an appropriate management approach. Abstract Introduction: Hemifacial microsomia (HFM) is the second most common congenital craniofacial malformation after cleft lip and/or palate, characterized by facial asymmetry due to abnormal development of the first and second pharyngeal arches. Accessory auricle may occur as an isolated anomaly or as part of the HFM spectrum. This study also presents a scoping review of reported cases (2001–2024) to compare clinical findings and management approaches. Case Illustration: We report a one-year-old girl who presented with left-sided HFM and a left accessory auricle. Clinical findings included facial asymmetry, micrognathia, macrostomia, and a preauricular cartilaginous skin tag, without airway or feeding problems. 3D CT revealed hypoplasia of the left mandibular condyle and temporomandibular joint, with no intracranial abnormalities. Management included conservative observation of the mandibular deformity and surgical excision of the accessory auricle. Discussion: Accessory auricles may occur as isolated congenital anomalies or in association with craniofacial conditions such as hemifacial microsomia (HFM). Imaging plays an important role in assessing skeletal involvement and excluding intracranial abnormalities. In HFM patients without functional impairment, conservative management with regular monitoring of mandibular growth is appropriate. Surgical excision of accessory auricles is usually performed for aesthetic reasons and can be achieved with a simple procedure. Conclusion: In this case, the mandibular deformity was managed conservatively with observation, while the accessory auricle was treated with surgical excision and primary closure, followed by routine wound care, with satisfactory outcomes.